Protected grounds of discrimination and the risk of workplace bullying - Michael Rosander; Helge Hoel; Stefan Blomberg (Frontiers in Psychology)
The present study investigated the protected grounds of discrimination and the risk of exposure to workplace bullying when being in a minority at work—feeling like a minority—or merely belonging to a protected group. Further we elucidated the boundary between bullying and discrimination. Based on a social identity perspective we tested hypotheses on the risks of bullying using a probability sample of the Swedish workforce. The results showed an increased risk of person-related bullying for employees who have a protected characteristic (OR = 1.87). When also feeling like a minority the risk increased substantially (OR = 5.13). Particular high risks were found for disabled and those from an ethnic minority. The risk is not merely a structural problem affecting all where bullying is construed from being treated unfairly as part of a wider collective; the results showed an increased risk of bullying of individual targets having a protected characteristic. To alleviate this requires a comprehensive approach involving policies treating it as an organizational issue, proactively as well as having safe procedures when problems surface. Creating more well-functioning workplaces will alleviate the problem for all, although to succeed those with protected characteristics would need particular consideration.